Respostas

2013-07-18T11:44:57-03:00
2013-07-18T12:55:32-03:00
A  formula  seria  (2*i -j )                  i (1 0 )  2*1 -1 = 1                                                                                                                   (3 0 )   2*1 -1 = 3                                                                                                                    j         2*1 -2 = 0                                                                                                                            2*2 -2 = 2